Public administration education and Europeanization: prospects for the emancipation of a discipline? - Verheijen, Tony; Connaughton, Bernadette (2003)
The twin processes of Europeanization and Transition provide significant opportunities for the development of public administration education in Europe and provide a possibility to further the `emancipation' of the discipline. In terms of Europeanization, the increasing challenges of politico-administrative interaction between national administrations and the institutions of the European Union illustrate that it is essential for public administration graduates to acquire an informed understanding of both the European context of policy-making and of the administrative organization and culture of other member states and countries associated with the EU. As a second element, the transition process in Central and Eastern European states could provide the discipline with further impetus to search for its own identity and approach in a European context. This article reviews the key findings of the results of the comprehensive inventories undertaken by the SOCRATES Thematic Network in public administration with regard to the current direction in which public administration education in Europe is moving. It addresses whether attention to European issues is reflected in the curriculum as well as links with the profession and whether cross-fertilization between the development of new programmes in the transition states and PA academic programmes in the EU member states has actually occurred. - Reproduced.
Keywords: Public administration